A New Lithium‐Ion Conductor LiTaSiO5: Theoretical Prediction, Materials Synthesis, and Ionic Conductivity. (7th July 2019) - Wang, Qi; Wu, Jian‐Fang; Lu, Ziheng; Ciucci, Francesco; Pang, Wei Kong; Guo, Xin
Abstract: Owing to the nonleakage and incombustibility, solid electrolytes are crucial for solving the safety issues of rechargeable lithium batteries. In this work, a new class of solid electrolyte, acceptor‐doped LiTaSiO5, is designed and synthesized based on the concerted migration mechanism. When Zr 4+ is doped to the Ta 5+ sites in LiTaSiO5, the high‐energy lattice sites are partly occupied by the introduced lithium ions, and the lithium ions at those sites interact with the lithium ions placed in the low‐energy sites, thereby favoring the concerted motion of lithium ions and lowering the energy barrier for ion transport. Therefore, the concerted migration of lithium ions occurs in Zr‐doped LiTaSiO5, and a 3D lithium‐ion diffusion network is established with quasi‐1D chains connected through interchain channels. The lithium‐ion occupation, as revealed by ab initio calculations, is validated by neutron powder diffraction. Zr‐doped LiTaSiO5 electrolytes are successfully synthesized; Li1.1 Ta0.9 Zr0.1 SiO5 shows a conductivity of 2.97 × 10 −5 S cm −1 at 25 °C, about two orders of magnitude higher than that of LiTaSiO5, and it increases to 3.11 × 10 −4 S cm −1 at 100 °C. This work demonstrates the power of theory in designing new materials. Abstract : A new class of lithium‐ion conductors, acceptor‐doped LiTaSiO5, is designed and synthesized. By doping Zr 4+ at the Ta 5+ sites, extra lithium ions are introduced into LiTaSiO5, which partly occupy the high‐energy sites and interact with lithium ions at the low‐energy sites, and then a 3D diffusion network is formed, resulting in fast ion migration and a high ionic conductivity.